The crazy project – Canal Istanbul - Kundak, Seda; Baypınar, Mete Başar (TeMA - Journal of Land Use, Mobility and Environment, 2011)
It was late April 2011 when “the Crazy Project - Canal Istanbul” was proposed by the Prime Minister of Turkey, during his election campaign. Although the idea of an artificial canal is not new, since it is initiated without any consensus between the people and institutions in Istanbul, the project immediately set a large number of debates. These vary from the legitimacy of decentralization of governance, to potential impacts of the canal on international politics, economy, environment and urban life. Regarding past infrastructure projects in Istanbul, such large scale investments have caused extensive acceleration in construction sector in one hand and social and economic shifts on the other. In this paper, the Canal Istanbul Project is evaluated according to basic motivations and claims of the PM, multi-perspective view through challenges and limitation that the project is likely to face with and speculations on implementation approach. The final discussion on the project is based on benefits/losses of Istanbul once the project will be implemented.